Adhesive for semiconductor, semiconductor device and method for manufacturing the same

By using a semiconductor adhesive containing a high content of inorganic filler, the problem of heat accumulation in high functional and highly integrated packages is solved, and excellent heat dissipation and higher semiconductor chip reliability are achieved.

CN115298280BActive Publication Date: 2025-04-08RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180021009.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-04-01
Filing Date
2021-03-25
Publication Date
2025-04-08
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

In highly functional and highly integrated semiconductor packages, narrowing of wiring spacing leads to an increase in the package's heat generation, and if heat accumulation is accumulated, it may cause semiconductor chip failure, and the heat dissipation of existing adhesives is insufficient.

Method used

A semiconductor adhesive containing a curable resin, a flux and an inorganic filler is provided, with an inorganic filler content of 60 to 95 mass%, and a heat conductivity after curing is 1.5 W/mK or more, which is suitable for sealing the connecting portion.

Benefits of technology

It achieves excellent heat dissipation, effectively reduces the heat accumulation of the package, and improves the reliability and performance of semiconductor chips.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115298280B_ABST
    Figure CN115298280B_ABST
Patent Text Reader

Abstract

A semiconductor adhesive is used for sealing a connection portion in a semiconductor device having a connection structure in which respective connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other and / or a connection structure in which respective connection portions of a plurality of semiconductor chips are electrically connected to each other. The semiconductor adhesive contains a curable resin component, a flux and an inorganic filler, the content of the inorganic filler is 60 to 95% by mass based on the total amount of the semiconductor adhesive, and the thermal conductivity of the semiconductor adhesive after curing is 1.5 W / mK or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive for semiconductors, a semiconductor device and a method for manufacturing the same. Background Art

[0002] In the past, wire bonding methods using fine metal wires such as gold wires were widely used to connect semiconductor chips and substrates. However, in order to meet the requirements for high functionality, high integration, and high speed of semiconductor devices, flip-chip connection methods (FC connection methods) that form conductive protrusions called bumps on semiconductor chips or substrates and directly connect semiconductor chips and substrates are becoming increasingly popular.

[0003] As flip chip connection methods, there are known methods of metal bonding using solder, tin, gold, silver, copper, etc., methods of metal bonding by applying ultrasonic vibration, methods of maintaining mechanical contact by the shrinkage force of resin, etc. However, from the perspective of reliability of the connection part, the method of metal bonding using solder, tin, gold, silver, copper, etc. is generally adopted.

[0004] For example, the COB (Chip On Board) connection method widely used in BGA (Ball Grid Array) and CSP (Chip Size Package) for connecting semiconductor chips to substrates is also a flip-chip connection method. Furthermore, the flip-chip connection method is also widely used in COC (Chip On Chip) connection methods, which connect semiconductor chips by forming bumps or wiring on the semiconductor chip (for example, see Patent Document 1 below).

[0005] With the growing demand for further miniaturization, thinning, and enhanced functionality, chip stacking, POP (Package on Package), and TSV (Through-Silicon Via), which combine the aforementioned connection methods and create multiple layers, are becoming increasingly popular. These technologies are widely used because they enable smaller packages by creating a three-dimensional rather than a flat configuration. They are also effective in improving semiconductor performance, reducing noise, reducing mounting area, and conserving power, and are attracting attention as next-generation semiconductor wiring technologies.

[0006] Previous technical literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 2008-294382 Summary of the Invention

[0009] Technical issues to be solved by the invention

[0010] In the above-mentioned flip-chip connection method, flip-chip connection is sometimes performed through a semiconductor adhesive for the purpose of protecting the metal bonding at the connection portion.

[0011] In recent years, flip-chip packaging has seen a continuous increase in functionality and integration. However, this progress has led to narrower wiring pitches, increasing package heat generation. Heat accumulation within the package can cause the semiconductor chip to reach high temperatures, potentially leading to failure. Consequently, semiconductor adhesives are required to exhibit superior heat dissipation properties.

[0012] Therefore, an object of the present invention is to provide a semiconductor adhesive having excellent heat dissipation properties, and another object of the present invention is to provide a semiconductor device using such a semiconductor adhesive and a method for manufacturing the same.

[0013] Means for solving technical problems

[0014] One embodiment of the present invention provides a semiconductor adhesive used for sealing connection portions in a semiconductor device having a connection structure in which connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other, and / or a connection structure in which connection portions of a plurality of semiconductor chips are electrically connected to each other. The semiconductor adhesive contains a curable resin component, a flux, and an inorganic filler, wherein the content of the inorganic filler is 60 to 95% by mass based on the total amount of the semiconductor adhesive, and the thermal conductivity of the semiconductor adhesive after curing is 1.5 W / mK or greater.

[0015] The inorganic filler may contain polyhedral alumina.

[0016] The inorganic filler may include at least one selected from the group consisting of silicon carbide, boron nitride, diamond, silicon dioxide, and aluminum nitride.

[0017] The inorganic filler may have peaks in each of the ranges of 0.1 to 4.5 μm and 5 to 20 μm in the volume-based particle size distribution.

[0018] The semiconductor binder may include, as inorganic fillers, polyhedral alumina having a volume-based average particle size r1 of 5 to 20 μm and polyhedral alumina having a volume-based average particle size r2 of 0.1 to 4.5 μm.

[0019] The difference (r1-r2) between the average particle diameter r1 and the average particle diameter r2 may be 4 to 10 μm.

[0020] The thermal conductivity of the adhesive for semiconductors after curing may be 3.0 W / mK or higher.

[0021] The fluxing agent may be a carboxylic acid.

[0022] The curable resin component may contain a thermosetting resin, a curing agent, and a thermoplastic resin.

[0023] Another embodiment of the present invention provides a method for manufacturing a semiconductor device, wherein the semiconductor device has a connection structure in which the respective connection portions of a semiconductor chip and a wiring circuit substrate are electrically connected to each other and / or a connection structure in which the respective connection portions of a plurality of semiconductor chips are electrically connected to each other, and the method for manufacturing the semiconductor device includes: a step of sealing at least a portion of the connection portion using the above-mentioned semiconductor adhesive.

[0024] Another embodiment of the present invention provides a semiconductor device comprising: a connection structure in which respective connection portions of a semiconductor chip and a wiring circuit substrate are electrically connected to each other and / or a connection structure in which respective connection portions of a plurality of semiconductor chips are electrically connected to each other; and a sealing material for sealing at least a portion of the connection portion, the sealing material containing a cured product of the above-mentioned adhesive for semiconductors.

[0025] Effects of the Invention

[0026] According to the present invention, a semiconductor adhesive having excellent heat dissipation properties can be provided. In addition, according to the present invention, a semiconductor device using such a semiconductor adhesive and a method for manufacturing the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic cross-sectional view showing one embodiment of a semiconductor device according to the present invention.

[0028] Figure 2 It is a schematic cross-sectional view showing another embodiment of the semiconductor device according to the present invention.

[0029] Figure 3 It is a schematic cross-sectional view showing another embodiment of the semiconductor device according to the present invention.

[0030] Figure 4 Yes Figure 3 A schematic cross-sectional view of an example of a method for manufacturing a semiconductor device shown.

[0031] Figure 5 It is a schematic cross-sectional view showing another embodiment of the semiconductor device according to the present invention. DETAILED DESCRIPTION

[0032] The following describes in detail embodiments of the present invention with reference to the drawings as appropriate. However, the present invention is not limited to the following embodiments. In this specification, "(meth)acrylic acid" refers to acrylic acid or methacrylic acid, and "(meth)acrylate" refers to acrylate or its corresponding methacrylate. "A or B" may include either A or B, or both.

[0033] Furthermore, in this specification, a numerical range expressed using "to" indicates a range including the numerical values ​​before and after "to" as the minimum and maximum values, respectively. Furthermore, within the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range at a certain stage may be replaced by the upper limit or lower limit of a numerical range at another stage. Furthermore, within the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced by the values ​​shown in the Examples.

[0034] <Adhesives for semiconductors>

[0035] The semiconductor adhesive involved in this embodiment is a semiconductor adhesive used for sealing the connection portions in a semiconductor device having a connection structure in which the respective connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other, and / or a connection structure in which the respective connection portions of multiple semiconductor chips are electrically connected to each other. The semiconductor adhesive contains a curable resin component, a flux, and an inorganic filler. The content of the inorganic filler is 60 to 95% by mass based on the total amount of the semiconductor adhesive. The thermal conductivity of the semiconductor adhesive after curing is 1.5 W / mK or greater.

[0036] (Curing resin component)

[0037] The curable resin component may contain (a) a thermosetting resin, (b) a curing agent, and (c) a thermoplastic resin.

[0038] (a) Thermosetting resin

[0039] Examples of thermosetting resins include epoxy resins, urea-formaldehyde resins, melamine resins, and phenolic resins. From the perspective of good curability and excellent adhesion, epoxy resins can be used as the thermosetting resin. Thermosetting resins can be used alone or in combination of two or more.

[0040] Examples of the epoxy resin include epoxy resins having two or more epoxy groups in the molecule, such as bisphenol A epoxy resins, bisphenol F epoxy resins, naphthalene epoxy resins, phenol novolac epoxy resins, cresol novolac epoxy resins, phenol aralkyl epoxy resins, biphenyl epoxy resins, triphenylmethane epoxy resins, dicyclopentadiene epoxy resins, and various polyfunctional epoxy resins. These epoxy resins can be used alone or in combination of two or more.

[0041] The epoxy resin content may be 40 parts by mass or more or 50 parts by mass or less, or 90 parts by mass or less or 80 parts by mass or less, per 100 parts by mass of the curing agent resin component.

[0042] The epoxy resin content can be 10 parts by mass or more, or 20 parts by mass or more, relative to 100 parts by mass of the semiconductor adhesive. The epoxy resin content can be 50 parts by mass or less, or 40 parts by mass or less, relative to 100 parts by mass of the semiconductor adhesive. The epoxy resin content can be 10 to 50 parts by mass relative to 100 parts by mass of the semiconductor adhesive.

[0043] (b) Curing agent

[0044] Examples of curing agents include phenolic resin curing agents, acid anhydride curing agents, amine curing agents, imidazole curing agents, and phosphine curing agents. Curing agents containing phenolic hydroxyl groups, acid anhydrides, amines, or imidazoles are more likely to exhibit fluxing activity that suppresses the formation of oxide films at the connection points, thereby improving connection reliability and insulation reliability.

[0045] As the phenolic resin curing agent, for example, a curing agent having two or more phenolic hydroxyl groups in the molecule can be mentioned, and phenol novolac, cresol novolac, phenol aralkyl resin, cresol naphthol formaldehyde polycondensate, triphenylmethane type polyfunctional phenol, various polyfunctional phenolic resins, etc. can be used. The phenolic resin curing agent can be used alone or in combination of two or more.

[0046] When the curable resin component contains an epoxy resin, the equivalent ratio (phenolic hydroxyl group / epoxy group, molar ratio) of the phenolic resin curing agent to the epoxy resin can be 0.3-1.5, 0.4-1.0, or 0.5-1.0 from the viewpoint of excellent curability, adhesion, and storage stability. An equivalent ratio of 0.3 or greater tends to improve curability and adhesion, while an equivalent ratio of 1.5 or less tends to prevent excessive unreacted phenolic hydroxyl groups from remaining, thereby suppressing water absorption and further improving insulation reliability.

[0047] Examples of the acid anhydride curing agent include methylcyclohexanetetracarboxylic dianhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and ethylene glycol bis-trimellitic anhydride.

[0048] When the curable resin component contains an epoxy resin, the equivalent ratio (anhydride group / epoxy group, molar ratio) of the acid anhydride curing agent to the epoxy resin may be 0.3 to 1.5, 0.4 to 1.0, or 0.5 to 1.0 from the perspective of excellent curability, adhesion, and storage stability. An equivalent ratio of 0.3 or greater tends to improve curability and adhesion, while an equivalent ratio of 1.5 or less tends to prevent excessive unreacted anhydride from remaining, keeping water absorption low, and further improving insulation reliability.

[0049] Examples of the amine-based curing agent include dicyandiamide.

[0050] When the curable resin component contains an epoxy resin, the equivalent ratio (amine / epoxy group, molar ratio) of the amine curing agent to the epoxy resin may be 0.3-1.5, 0.4-1.0, or 0.5-1.0 from the perspective of excellent curability, adhesion, and storage stability. An equivalent ratio of 0.3 or greater tends to improve curability and adhesion, while an equivalent ratio of 1.5 or less tends to prevent excessive unreacted amine from remaining, further improving insulation reliability.

[0051] Examples of the imidazole curing agent include 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6- [2'-Undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and adducts of epoxy resins and imidazoles. Among them, from the viewpoint of better curability, storage stability and connection reliability, the imidazole curing agent may be 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole and 2-phenyl-4-methyl-5-hydroxymethylimidazole. The imidazole curing agent may be used alone or in combination of two or more. Furthermore, these can also be used as microencapsulated latent curing agents.

[0052] The content of the imidazole curing agent can be 0.1 to 20 parts by mass, 0.1 to 10 parts by mass, 0.1 to 5 parts by mass, or 0.5 to 5 parts by mass relative to 100 parts by mass of the curable resin component. When the content of the imidazole curing agent is 0.1 parts by mass or more, curability tends to be improved, while when it is 20 parts by mass or less, the adhesive composition does not cure before metal bonding is achieved, and poor connection tends to be less likely to occur.

[0053] Examples of the phosphine-based curing agent include triphenylphosphine, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetrakis(4-methylphenyl)borate, and tetraphenylphosphonium (4-fluorophenyl)borate.

[0054] The content of the phosphine-based curing agent can be 0.1 to 10 parts by mass or 0.1 to 5 parts by mass relative to 100 parts by mass of the curable resin component. When the content of the phosphine-based curing agent is 0.1 parts by mass or greater, curability tends to be improved. When the content is 10 parts by mass or less, the semiconductor adhesive does not cure before metal bonding is formed, which tends to make poor connection less likely to occur.

[0055] Phenolic resin curing agents, acid anhydride curing agents, and amine curing agents can be used alone or in combination of two or more. Imidazole curing agents and phosphine curing agents can be used alone or in combination with phenolic resin curing agents, acid anhydride curing agents, or amine curing agents.

[0056] As a curing agent, from the perspective of excellent curing properties, a phenolic resin curing agent and an imidazole curing agent can be used simultaneously, an anhydride curing agent and an imidazole curing agent can be used simultaneously, an amine curing agent and an imidazole curing agent can be used simultaneously, or an imidazole curing agent can be used alone. Since productivity is improved when connecting in a short time, an imidazole curing agent with excellent fast curing properties can be used alone. In this case, volatile components such as low molecular weight components can be suppressed during curing in a short time, and therefore, the formation of voids can also be easily suppressed.

[0057] The content of the curing agent may be 0.1 to 20 parts by mass or 0.1 to 10 parts by mass relative to 100 parts by mass of the curable resin component.

[0058] ((c) Thermoplastic resin)

[0059] As thermoplastic resins, phenoxy resins, polyimide resins, polyamide resins, polycarbodiimide resins, cyanate resins, (meth) acrylic resins, polyester resins, polyethylene resins, polyethersulfone resins, polyetherimide resins, polyvinyl acetal resins, carbamate resins, acrylic rubbers, etc. can be mentioned. As thermoplastic resins, from the viewpoint of excellent heat resistance and film forming properties, phenoxy resins, polyimide resins, (meth) acrylic resins, acrylic rubbers, cyanate resins, polycarbodiimide resins, etc. can be mentioned. Phenoxy resins, polyimide resins, (meth) acrylic resins, acrylic rubbers can be mentioned. Thermoplastic resins can be used alone or in combination of two or more.

[0060] Examples of phenoxy resins include ZX1356-2 and FX-293 manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Urethane resins include T-8175N manufactured by DIC Covestro Polymer Ltd., which is a polyurethane. (Meth)acrylic resins include acrylic block copolymers, which are block copolymers of at least one of (meth)acrylic acid, (meth)acrylic acid esters, and (meth)acrylic acid methyl esters. (Meth)acrylic block copolymers include LA4285, LA2330, and LA2140 (all manufactured by KURARAY CO., LTD.), which are block copolymers of methyl methacrylate and butyl acrylate. From the perspective of achieving superior heat dissipation, the thermoplastic resin may be a phenoxy resin having a structure that easily adopts a crystalline structure (a structure with many aromatic rings).

[0061] From the perspective of excellent adhesion of the semiconductor adhesive to the substrate and chip, the glass transition temperature (Tg) of the thermoplastic resin can be 120°C or lower, 100°C or lower, or 85°C or lower. When the semiconductor adhesive contains a thermoplastic resin with a Tg of 120°C or lower, the curing reaction can be suppressed, making it easier to embed the bumps formed on the semiconductor chip and the electrodes and wiring patterns formed on the substrate. This reduces the likelihood of bubbles remaining and tends to suppress the formation of voids. Furthermore, when the semiconductor adhesive contains a thermoplastic resin with a Tg above room temperature (25°C), the semiconductor adhesive can be easily formed into a thin film or membrane.

[0062] In this specification, Tg of a thermoplastic resin refers to Tg measured using differential scanning calorimetry (DSC, DSC-7 manufactured by PerkinElmer Co., Ltd.) under the conditions of a sample amount of 10 mg, a heating rate of 10°C / min, and a measurement atmosphere of air.

[0063] From the perspective of excellent film formability of the semiconductor adhesive, the weight average molecular weight of the thermoplastic resin may be 10,000 or greater, 30,000 or greater, 40,000 or greater, or 50,000 or greater. From the perspective of excellent film processability of the semiconductor adhesive, the weight average molecular weight of the thermoplastic resin may be 1,000,000 or less, or 500,000 or less.

[0064] In this specification, the weight average molecular weight refers to a weight average molecular weight measured in terms of polystyrene using a high performance liquid chromatography (C-R4A manufactured by Shimadzu Corporation).

[0065] When the curable resin component contains an epoxy resin and a thermoplastic resin, the epoxy resin content can be 1 part by mass or more, 5 parts by mass or more, or 10 parts by mass or more, and can be 500 parts by mass or less, 400 parts by mass or less, or 300 parts by mass or less, per 100 parts by mass of the thermoplastic resin. The epoxy resin content can be 1 to 500 parts by mass, 5 to 400 parts by mass, or 10 to 300 parts by mass per 100 parts by mass of the thermoplastic resin. When the epoxy resin content is within these ranges, the semiconductor adhesive exhibits sufficient curability, excellent adhesive strength, and is easily formed into a film or membrane.

[0066] The content of the thermoplastic resin may be 0.1 parts by mass or more, 1 part by mass or more, or 10 parts by mass or more, and may be 50 parts by mass or less, or 40 parts by mass or less, relative to 100 parts by mass of the curable resin component. The content of the thermoplastic resin may be 0.1 to 50 parts by mass, 1 to 50 parts by mass, or 10 to 40 parts by mass relative to 100 parts by mass of the curable resin component.

[0067] The content of the curable resin component can be 10% by mass or more, or 30% by mass or more, and can be 70% by mass or less, or 50% by mass or less, based on the total amount of the adhesive for semiconductors. The content of the curable resin component can be 10-70% by mass, 10-50% by mass, or 30-50% by mass, based on the total amount of the adhesive for semiconductors.

[0068] (Flux)

[0069] The semiconductor adhesive according to this embodiment may further contain a flux (i.e., a flux activator exhibiting flux activity (activity in removing oxides, impurities, etc.)). Examples of the flux include nitrogen-containing compounds having unshared electron pairs (imidazoles, amines, etc.), carboxylic acids, phenols, and alcohols.

[0070] The flux may contain an organic acid that reacts with the epoxy resin from the viewpoint of exhibiting stronger flux activity than alcohols and easily improving connectivity.

[0071] When the curable resin component contains an epoxy resin, it reacts with the epoxy resin and does not exist in a free state in the cured product of the semiconductor adhesive, thereby preventing a decrease in insulation reliability. Therefore, it may contain an organic acid or a carboxylic acid.

[0072] Examples of carboxylic acids include: aliphatic saturated carboxylic acids such as ethane, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, heptadecanoic acid, and octadecanoic acid; aliphatic unsaturated carboxylic acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, docosahexaenoic acid, and eicosapentaenoic acid; aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, trimesic acid, pyromellitic acid, pentanecarboxylic acid, and mesic acid; maleic acid and fumaric acid. Examples of carboxylic acids having a hydroxyl group include lactic acid, malic acid, citric acid, and salicylic acid.

[0073] The carboxylic acid may be a dicarboxylic acid. Since dicarboxylic acids are relatively less volatile than monocarboxylic acids, they tend to suppress voids. Furthermore, compared to tricarboxylic acids, dicarboxylic acids are less likely to react at low temperatures (temperatures below bonding, e.g., below 100°C) during film formation, lamination, and preheating. Therefore, the viscosity does not become excessively high, which tends to suppress poor connection.

[0074] The carboxylic acid may be a carboxylic acid having one or more alkyl groups at the 2nd or 3rd position from the carboxyl group. Examples of the carboxylic acid having such an alkyl group include 2-methylglutaric acid and 3-methylglutaric acid.

[0075] The flux content can be 0.5 parts by mass or more, 1 part by mass or more, or 1.5 parts by mass or more relative to 100 parts by mass of the semiconductor adhesive. The flux content can be 10 parts by mass or less, or 5 parts by mass or less relative to 100 parts by mass of the semiconductor adhesive. The flux content can be 0.5 to 10 parts by mass, or 0.5 to 5 parts by mass relative to 100 parts by mass of the semiconductor adhesive.

[0076] (Inorganic filler)

[0077] The semiconductor adhesive of this embodiment contains an inorganic filler. The content of the inorganic filler is 60-95% by mass based on the total amount of the semiconductor adhesive. If the content of the inorganic filler is within this range, the semiconductor adhesive can be endowed with excellent heat dissipation properties.

[0078] Examples of the inorganic filler include aluminum oxide (Al2O3), magnesium oxide, silicon carbide, boron nitride, diamond, and aluminum nitride. From the perspective of thermal conductivity of the semiconductor adhesive, the inorganic filler may contain at least one selected from the group consisting of aluminum oxide, silicon carbide, boron nitride, diamond, and aluminum nitride.

[0079] When the inorganic filler is particles containing aluminum oxide (hereinafter also referred to as "alumina filler"), the aluminum oxide may be α-alumina. From the perspective of excellent heat dissipation in the semiconductor adhesive, the aluminum oxide purity of the alumina filler may be 99.0% by mass or greater, 99.5% by mass or greater, or 99.9% by mass or greater. The alumina filler may be substantially composed of aluminum oxide (100% by mass of the alumina filler being substantially aluminum oxide).

[0080] The shape of the alumina filler is not particularly limited, and examples thereof include spherical, roughly spherical, polyhedral, needle-shaped, and plate-shaped. From the perspective of excellent heat dissipation of the adhesive for semiconductors, it may be spherical or polyhedral, and may be a polyhedron. In addition, in this specification, "polyhedron" refers to a solid having multiple planes as a component of the surface. Multiple planes may also intersect via curved surfaces (they may have rounded corners). For example, a polyhedron may have 4 to 100 planes as a component of the surface.

[0081] The reason why the use of polyhedral alumina as the alumina filler improves the heat dissipation properties of the semiconductor adhesive is not necessarily clear, but the present inventors believe that the polyhedral alumina filler allows the fillers to contact each other at their surfaces, increasing the heat transfer area and improving heat transfer.

[0082] From the perspective of improving film-forming properties when the semiconductor adhesive is formed into a thin film, the average particle size of the inorganic filler may be 20 μm or less, 15 μm or less, or 10 μm or less. From the perspective of dispersibility of the inorganic filler, the average particle size of the inorganic filler may be 0.1 μm or more, 0.5 μm or more, or 1 μm or more.

[0083] In this specification, the "average particle size" refers to the particle size at a point corresponding to 50% volume when the cumulative frequency distribution curve based on the particle size is obtained with the total volume of the particles as 100%, and can be measured using a particle size distribution measuring device using a laser diffraction scattering method.

[0084] From the perspective of further improving visibility, dispersibility, and adhesive strength, the alumina filler may be an alumina filler having a surface treatment. Examples of surface treatment agents include glycidyl (epoxy) compounds, amine compounds, phenyl compounds, phenylamino compounds, (meth)acrylic compounds (e.g., compounds having a structure represented by the following general formula (1)), and vinyl compounds having a structure represented by the following general formula (2).

[0085]

[0086] [R 11 represents a hydrogen atom or an alkyl group, R12 represents an alkylene group.]

[0087] Examples of fillers surface-treated with a compound having a structure represented by formula (1) include R 11 Acrylic surface treated filler with hydrogen atoms, R 11 Methacrylic acid surface treated filler, R 11 Ethyl acrylic acid surface treated filler etc. which is ethyl. From the viewpoint of reactivity with the resin contained in the semiconductor adhesive and the surface of the semiconductor substrate, and bond formation, R 11 It can be a hydrogen atom or a methyl group as a small substituent. The surface treated filler can be an acrylic acid surface treated filler or a methacrylic acid surface treated filler. 12 The alkylene group is not particularly limited, but may have a high weight average molecular weight from the viewpoint of reducing volatile components.

[0088]

[0089] [R 21 、R 22 and R 23 Each independently represents a hydrogen atom or an alkyl group, R 24 represents an alkylene group.]

[0090] From the viewpoint of not reducing the reactivity, R 21 、R 22 and R 23 It can be a small substituent. Also, it can be a substituent that improves the reactivity of the vinyl group in formula (2). 24 There are no particular restrictions, but from the perspective of low volatility and reduction of voids, a group with a high weight average molecular weight may be used. 21 、R 22 、R 23 and R 24 You can also select according to the difficulty of surface treatment. 21 、R 22 and R 23 A hydrogen atom or a methyl group may also be used.

[0091] Surface treatment agents, from the perspective of ease of surface treatment, may be silane compounds such as epoxy silanes, amino silanes, (meth)acrylic silanes, and vinyl silanes. Furthermore, from the perspective of achieving greater transparency in the semiconductor adhesive, the alumina filler may be an alumina filler whose surface has been silane-treated. Surface treatment agents, from the perspective of excellent dispersibility, fluidity, and adhesion, may be glycidyl, phenylamino, (meth)acrylic, or vinyl silane compounds. Surface treatment agents, from the perspective of excellent storage stability, may be vinyl, phenylamino, or (meth)acrylic silane compounds.

[0092] The inorganic filler may be used alone or in combination of two or more different types. For example, the inorganic fillers used in combination may be two or more different types, such as alumina filler and silicon carbide filler. Furthermore, the inorganic fillers used in combination may be two or more of the same type, differing in shape, average particle size, surface treatment, etc.

[0093] From the viewpoint of further improving heat dissipation, the inorganic fillers used simultaneously may be two or more inorganic fillers of the same kind, two or more alumina fillers, two or more polyhedral aluminas, or two or more polyhedral aluminas having different average particle sizes.

[0094] When two or more inorganic fillers are used, from the perspective of achieving better heat dissipation, the inorganic filler may have multiple peaks in its volume-based particle size distribution, and may have peaks in the ranges of 0.1 to 4.5 μm and 5 to 20 μm, respectively. In this specification, "peak" refers to the maximum value of the number frequency in the volume-based particle size distribution.

[0095] From the perspective of better heat dissipation, one of the multiple peaks (the first peak) may be 5 to 15 μm, 5 to 10 μm, or 5 to 8 μm. From the perspective of better heat dissipation, one of the multiple peaks (the second peak) may be 0.1 to 3.0 μm, 0.1 to 2.0 μm, or 0.1 to 1.5 μm.

[0096] From the perspective of better heat dissipation, the difference between the peak positions of the first and second peaks may be 4 μm or more, or 5 μm or more, and may be 10 μm or less, 8 μm or less, or 7 μm or less. The difference between the peak positions of the first and second peaks may be 4 to 10 μm, 4 to 8 μm, or 5 to 7 μm.

[0097] An inorganic filler having multiple peaks in the volume-based particle size distribution can be obtained by using two or more inorganic fillers having different mode diameters or average particle sizes. For example, the inorganic fillers used together may have a mode diameter or average particle size of 5 to 20 μm and an inorganic filler having a mode diameter or average particle size of 0.1 to 4.5 μm.

[0098] To achieve better heat dissipation, the semiconductor adhesive can be formulated with a first inorganic filler having a mode diameter or average particle size of 5 to 20 μm and a second inorganic filler having a mode diameter or average particle size of 0.1 to 4.5 μm. The mode diameter or average particle size of the first inorganic filler can be 5 to 15 μm, 5 to 10 μm, or 5 to 8 μm. The mode diameter or average particle size of the second inorganic filler can be 0.1 to 3.0 μm, 0.1 to 2.0 μm, or 0.1 to 1.5 μm.

[0099] To achieve even better heat dissipation, the semiconductor adhesive can be formulated with a first polyhedral alumina having an average particle size r1 of 5 to 20 μm and a second polyhedral alumina having an average particle size r2 of 0.1 to 4.5 μm. The average particle size r1 of the first polyhedral alumina can be 5 to 15 μm, 5 to 10 μm, or 5 to 8 μm. The average particle size r2 of the second polyhedral alumina can be 0.1 to 3.0 μm, 0.1 to 2.0 μm, or 0.1 to 1.5 μm.

[0100] From the viewpoint of achieving better heat dissipation, the difference (r1-r2) between the average particle size r1 of the first polyhedral alumina and the average particle size r2 of the second polyhedral alumina may be 4 to 10 μm, 4 to 8 μm, or 5 to 7 μm.

[0101] The blending amounts of the first and second polyhedral aluminas may be 10 to 70 parts by mass, 10 to 50 parts by mass, or 10 to 30 parts by mass of the second polyhedral alumina relative to 100 parts by mass of the first polyhedral alumina.

[0102] From the perspective of achieving even better heat dissipation, the content of the first polyhedral alumina in the semiconductor adhesive can be 60% by mass or more, or 70% by mass or more, and can be 90% by mass or less, or 85% by mass or less, based on the total amount of the semiconductor adhesive. The content of the first polyhedral alumina in the semiconductor adhesive can be 60-90% by mass, or 70-85% by mass, based on the total amount of the semiconductor adhesive.

[0103] From the perspective of achieving even better heat dissipation, the content of the second polyhedral alumina in the semiconductor adhesive can be 10% by mass or more, or 15% by mass or more, and can be 30% by mass or less, or 20% by mass or less, based on the total amount of the semiconductor adhesive. The content of the second polyhedral alumina in the semiconductor adhesive can be 10-30% by mass, or 15-20% by mass, based on the total amount of the semiconductor adhesive.

[0104] From the perspective of better heat dissipation, the content of the inorganic filler can be 75% by mass or more or 85% by mass or more based on the total amount of the semiconductor adhesive. In addition, when the inorganic filler is composed of two or more inorganic fillers, the content of the inorganic filler refers to the total amount of all the inorganic fillers.

[0105] When the inorganic filler is an alumina filler, the content of the alumina filler may be 75% by mass or more, or 85% by mass or more, based on the total amount of the semiconductor adhesive, from the perspective of achieving better heat dissipation. Furthermore, when the inorganic filler is two or more alumina fillers, the content of the alumina filler refers to the total amount of all alumina fillers.

[0106] When the inorganic filler is a mixture of two or more alumina fillers having different average particle sizes or mode diameters, the content of the alumina filler having the largest average particle size or mode diameter can be 60 to 90 mass % or 70 to 85 mass % based on the total amount of the semiconductor adhesive from the viewpoint of better heat dissipation.

[0107] (other)

[0108] The semiconductor adhesive of this embodiment may further contain additives such as organic fillers (resin fillers), antioxidants, silane coupling agents (excluding compounds that qualify as fluxing agents), titanium coupling agents, and leveling agents. These additives may be used alone or in combination of two or more. The content of these additives may be appropriately adjusted to maximize the effects of each additive.

[0109] As a material of the organic filler, polyurethane, polyimide, etc. can be used. Compared with inorganic fillers, resin fillers can impart flexibility at high temperatures such as 260°C, and thus are effective in improving thin film formability.

[0110] (Thermal conductivity)

[0111] The adhesive for semiconductors according to this embodiment has a thermal conductivity of 1.5 W / mK or more after curing. Setting the thermal conductivity of the adhesive for semiconductors to 1.5 W / mK or more after curing can provide an adhesive for semiconductors having excellent heat dissipation properties.

[0112] From the viewpoint of better heat dissipation, the thermal conductivity of the adhesive for semiconductor after curing may be 2.0 W / mK or more, 2.5 W / mK or more, 3.0 W / mK or more, 3.5 W / mK or more, or 4.0 W / mK or more.

[0113] The thermal conductivity of the cured semiconductor adhesive can be calculated by measuring thermal diffusivity using the Xe-flash method and multiplying the specific heat and density by the thermal diffusivity. Specifically, the thermal conductivity can be obtained by the method described in the Examples below.

[0114] The adhesive for a semiconductor can be cured by heating at 240° C. for 1 hour. Specifically, the cured adhesive for a semiconductor can be obtained by the method described in Examples below.

[0115] The semiconductor adhesive of this embodiment can be formed into a film or membrane. The thickness of the film or membrane-shaped semiconductor adhesive (film adhesive) can be, for example, 100 μm or less, 80 μm or less, or 50 μm or less. The lower limit of the thickness of the film adhesive is not particularly limited and can be 1 μm or more or 5 μm or more.

[0116] <Method for producing semiconductor adhesive>

[0117] Film-shaped or film-shaped adhesive for semiconductors can be obtained by the following method. First, after adding the above-mentioned curable resin component, flux, inorganic filler and other components to an organic solvent, the resin varnish is dissolved or dispersed by stirring, mixing, etc. Then, on the substrate film to which a demoulding process has been implemented, after applying the resin varnish using a knife coater, a roller coater, an applicator, a die coater, a comma coater, etc., the organic solvent is reduced by heating to form an adhesive for semiconductors on the substrate film. In addition, before the organic solvent is reduced by heating, the resin varnish can be spin-coated on a wafer, etc. to form a film, and then a method of drying the solvent can be used to form an adhesive for semiconductors on the wafer.

[0118] The substrate film is not particularly limited as long as it is a film having heat resistance capable of withstanding the heating conditions for volatilizing the organic solvent. Examples thereof include polyester film, polypropylene film, polyethylene terephthalate film, polyimide film, polyetherimide film, polyether naphthalate film, and methylpentene film. The substrate film is not limited to a single-layer film composed of one of these films, and may be a multilayer film composed of two or more films.

[0119] Specifically, the conditions for volatilizing the organic solvent from the applied resin varnish include heating at 50-200°C for 0.1-90 minutes. The organic solvent may be volatilized to 1.5% or less as long as it does not affect the gap after mounting or viscosity adjustment.

[0120] <Semiconductor Device>

[0121] A semiconductor device manufactured using the semiconductor adhesive according to this embodiment is described. The semiconductor device according to this embodiment includes a connection structure in which the respective connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other, and / or a connection structure in which the respective connection portions of multiple semiconductor chips are electrically connected to each other, and a sealing material that seals at least a portion of the connection portion, the sealing material containing a cured product of the semiconductor adhesive according to this embodiment. The connection portion in the semiconductor device can be either a metal bond between a bump and a wiring or a metal bond between bumps. In the semiconductor device according to this embodiment, for example, a flip-chip connection can be used in which electrical connection is achieved via the semiconductor adhesive.

[0122] Figure 1 Schematic cross-sectional view showing an embodiment of a semiconductor device (COB type connection method of a semiconductor chip and a substrate). Figure 1 As shown in (a), a semiconductor device 100 includes a semiconductor chip 10 and a substrate (circuit wiring substrate) 20 facing each other, wiring 15 arranged on the facing surfaces of the semiconductor chip 10 and the substrate 20, connection bumps 30 connecting the wiring 15 of the semiconductor chip 10 and the substrate 20, and a sealing material 40 seamlessly filling the gap between the semiconductor chip 10 and the substrate 20. The semiconductor chip 10 and the substrate 20 are flip-chip connected via the wiring 15 and the connection bumps 30. The wiring 15 and the connection bumps 30 are sealed by the sealing material 40 and isolated from the external environment. The sealing material 40 contains a cured product of the semiconductor adhesive according to this embodiment.

[0123] like Figure 1 As shown in FIG. 2( b ), a semiconductor device 200 includes a semiconductor chip 10 and a substrate 20 facing each other, bumps 32 disposed on the facing surfaces of the semiconductor chip 10 and the substrate 20, and a sealing material 40 seamlessly filling the gap between the semiconductor chip 10 and the substrate 20. The semiconductor chip 10 and the substrate 20 are connected to each other via the facing bumps 32, thereby forming a flip-chip connection. The bumps 32 are sealed by the sealing material 40 and isolated from the external environment.

[0124] Figure 2 1 is a schematic cross-sectional view showing another embodiment of a semiconductor device (a COC type connection method between semiconductor chips). Figure 2 As shown in (a), two semiconductor chips 10 are flip-chip connected by wiring 15 and connection bumps 30. Except for this, the semiconductor device 300 is the same as the semiconductor device 100. Figure 2 As shown in (b), the two semiconductor chips 10 are flip-chip connected via bumps 32 . Except for this, the semiconductor device 400 is the same as the semiconductor device 200 .

[0125] The semiconductor chip 10 is not particularly limited, and various semiconductors can be used, including elemental semiconductors made of the same element such as silicon and germanium, and compound semiconductors such as gallium arsenide and indium phosphide.

[0126] The substrate 20 is not particularly limited as long as it is a wiring circuit substrate. It can be a circuit substrate with wiring (wiring pattern) formed by etching away unnecessary parts of a metal layer formed on the surface of an insulating substrate mainly composed of glass epoxy, polyimide, polyester, ceramic, epoxy, bis(butylimide) triazine, polyimide, etc., a circuit substrate with wiring (wiring pattern) formed on the surface of the above-mentioned insulating substrate by metal electroplating, etc., and a circuit substrate with wiring (wiring pattern) formed by printing a conductive material on the surface of the above-mentioned insulating substrate.

[0127] Connection portions such as wiring 15 and bumps 32 contain gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper), nickel, tin, lead, etc. as main components, and may contain multiple metals.

[0128] A metal layer having gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper), tin, nickel, etc. as main components may also be formed on the surface of the wiring (wiring pattern). The metal layer may be composed of only a single component or multiple components. In addition, a structure in which multiple metal layers are stacked may also be provided. Since the metal layer is inexpensive and commonly used, copper or solder may be used, but since it contains oxides or impurities, flux activity is required.

[0129] As the material of the conductive protrusion called a bump, gold, silver, copper, solder (the main component is, for example, tin-silver, tin-lead, tin-bismuth, tin-copper), tin, nickel, etc. are used as the main components. It can be composed of only a single component or a plurality of components. In addition, it can also be formed into a structure in which these metals are stacked. The bump can also be formed on a semiconductor chip or a substrate. Because it is cheap and commonly used, the bump can be copper or solder, but because it contains oxides or impurities, flux activity is required.

[0130] Also, it can be stacked like Figure 1 or Figure 2The semiconductor device (package) shown is electrically connected using gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper), tin, nickel, etc. Copper and solder can be used for connection because they are inexpensive and commonly used, but flux activity is required because they contain oxides or impurities. For example, as seen in TSV technology, a semiconductor adhesive can be placed between semiconductor chips to perform flip-chip connection or stacking, forming a hole that penetrates the semiconductor chip and connects to the electrode on the pattern surface.

[0131] Figure 3 This is a schematic cross-sectional view showing another embodiment of a semiconductor device (a stacked semiconductor chip type (TSV)). Figure 3 In the semiconductor device 500 shown, the wiring 15 formed on the interposer 50 is connected to the wiring 15 of the semiconductor chip 10 via the connection bumps 30, thereby forming a flip-chip connection between the semiconductor chip 10 and the interposer 50. The gap between the semiconductor chip 10 and the interposer 50 is filled with a sealing material 40 without any gaps. On the surface of the semiconductor chip 10 opposite to the interposer 50, the semiconductor chip 10 is repeatedly stacked via the wiring 15, the connection bumps 30, and the sealing material 40. The wiring 15 on the pattern surface of the front and back of the semiconductor chip 10 is connected to each other via the through electrode 34 filled in the hole that penetrates the interior of the semiconductor chip 10. In addition, as the material of the through electrode 34, copper, aluminum, etc. can be used.

[0132] This TSV technology makes it possible to obtain signals from the backside of a semiconductor chip, which is not normally used. Furthermore, because the through-electrode 34 passes vertically through the interior of the semiconductor chip 10, the distance between opposing semiconductor chips 10 or between a semiconductor chip 10 and an interposer 50 can be shortened, enabling flexible connections. The semiconductor adhesive of this embodiment can be used as a sealing material between opposing semiconductor chips 10 or between a semiconductor chip 10 and an interposer 50 in this TSV technology.

[0133] Furthermore, in high-degree-of-freedom bump formation methods such as area bump chip technology, semiconductor chips can be directly mounted on a motherboard without interposing an interposer. The semiconductor adhesive of this embodiment is also applicable to situations where such semiconductor chips are directly mounted on a motherboard. Furthermore, the semiconductor adhesive of this embodiment is also applicable to sealing the gap between two wiring circuit boards when stacking them.

[0134] Figure 5 This is a schematic cross-sectional view showing another embodiment of a semiconductor device (a COB type connection method of a semiconductor chip and a substrate). Figure 5In the semiconductor device 600 shown, a substrate (glass epoxy substrate) 60 having wiring (copper wiring) 15 and a semiconductor chip 10 having wiring (copper pillars, copper posts) 15 are connected to each other via a sealing material 40. The wiring 15 of the semiconductor chip 10 and the wiring 15 of the substrate 60 are electrically connected via connection bumps (solder bumps) 30. A solder resist layer 70 is provided on the surface of the substrate 60 where the wiring 15 is formed, except for the positions where the connection bumps 30 are formed. The semiconductor chip 10 may have a through electrode.

[0135] <Method for Manufacturing Semiconductor Device>

[0136] In the manufacturing method of the semiconductor device involved in this embodiment, the semiconductor device has a connection structure in which the respective connection portions of a semiconductor chip and a wiring circuit substrate are electrically connected to each other and / or a connection structure in which the respective connection portions of a plurality of semiconductor chips are electrically connected to each other, and the manufacturing method of the semiconductor device includes: a step of sealing at least a portion of the connection portion using the semiconductor adhesive involved in this embodiment.

[0137] The above-mentioned steps can be performed by connecting a semiconductor chip and a wiring circuit board or a plurality of semiconductor chips to each other using the semiconductor adhesive according to this embodiment. In this case, the method for manufacturing a semiconductor device according to this embodiment may also include, for example, the steps of connecting the semiconductor chip and the wiring circuit board to each other via the semiconductor adhesive, and electrically connecting the respective connection portions of the semiconductor chip and the wiring circuit board to each other, and / or the steps of connecting the plurality of semiconductor chips to each other via the semiconductor adhesive, and electrically connecting the respective connection portions of the plurality of semiconductor chips to each other.

[0138] In the method for manufacturing a semiconductor device according to this embodiment, the connection portions can be connected to each other by metal bonding. That is, the connection portions of the semiconductor chip and the printed circuit board can be connected to each other by metal bonding, or the connection portions of the plurality of semiconductor chips can be connected to each other by metal bonding.

[0139] As an example of a method for manufacturing a semiconductor device according to this embodiment, Figure 31 and 2. The manufacturing method of the semiconductor device 500 shown in FIG. 1 is described. In the semiconductor device 500, the wiring (copper wiring) 15 formed on the interposer 50 is connected to the wiring (copper pillar, copper post) 15 of the semiconductor chip 10 via the connecting bumps (solder bumps) 30, thereby the semiconductor chip 10 and the interposer 50 are flip-chip connected. The gap between the semiconductor chip 10 and the interposer 50 is filled with a sealing material 40 without a gap. On the surface of the semiconductor chip 10 on the side opposite to the interposer 50, the semiconductor chip 10 is repeatedly stacked via the wiring 15, the connecting bumps 30 and the sealing material 40. The wiring 15 on the pattern surface of the front and back of the semiconductor chip 10 is connected to each other through the through electrode 34 filled in the hole that penetrates the interior of the semiconductor chip 10.

[0140] Figure 4 Is used to illustrate Figure 3 FIG. 1 is a diagram showing an example of a method for manufacturing a semiconductor device. Figure 4 (a) shows the step of press-bonding a stacked chip having a semiconductor adhesive applied to the main surface of a semiconductor chip to another semiconductor chip via the semiconductor adhesive. The stacked chip (stacked semiconductor chip) 700 includes a semiconductor chip 10 and a semiconductor adhesive 42 applied to the main surface of the semiconductor chip 10. The semiconductor chip 10 includes through electrodes 34 filling holes extending through the interior of the semiconductor chip 10, wiring 15 disposed on one surface of the semiconductor chip 10, and connection bumps 30 disposed on the wiring 15. The semiconductor adhesive 42 is applied to embed the wiring 15 and the connection bumps 30, but may cover at least a portion of the surface of the semiconductor chip 10, the wiring 15, and the connection bumps 30.

[0141] The stacked chip 700 can be produced by applying a semiconductor adhesive 42 onto a semiconductor wafer having wiring 15 and connection bumps 30, or by attaching the semiconductor adhesive 42 in a film form and then dicing the semiconductor chips 10 to separate them. The film-form semiconductor adhesive can be attached by heat pressing, roll lamination, vacuum lamination, or the like.

[0142] The laminated chip 700 can be crimped to another semiconductor chip by, for example, aligning the connection bumps 30 of the laminated chip 700 so that they are electrically connected to the through-electrodes 34 filled in the holes that penetrate the interior of the other semiconductor chip 10. The laminated chip 700 and the semiconductor chip 10 are then crimped using a crimping tool 90 while being heated to a temperature above the melting point of the connection bumps 30. (If solder is used for the connection, the temperature applied to the solder portion can be 240°C or higher.) This allows the laminated chip 700 to be connected to the semiconductor chip 10, and the connection portion is sealed by the cured semiconductor adhesive.

[0143] The connection load depends on the number of bumps, but can be set by taking into account the absorption of bump height deviations, the control of bump deformation, etc. From the perspective of improving productivity, the connection time can be short. The connection time can be the time required to melt the solder and remove the oxide film, surface impurities, etc., so that a metal joint can be formed at the connection portion. A short connection time (pressing time) refers to the time (for example, the time when solder is used) during which a temperature of 240°C or higher is applied to the connection portion during connection formation (formal pressing) for less than 10 seconds. The connection time can be less than 5 seconds or less than 3 seconds. The same method can also be applied to the connection between the interposer 50 having the wiring 15 and the stacked chip 700.

[0144] By repeating the above steps, it is possible to produce Figure 4 (b) The semiconductor device 500 shown. In addition, the semiconductor device 500 can also be manufactured by repeatedly aligning the stacked chip 700 and the semiconductor chip 10 and stacking them (temporarily fixing) to obtain a temporarily fixed multilayer stack, and then performing a heat treatment in a reflow furnace to melt the solder bumps and connect the semiconductor chips together. Since temporary fixing does not significantly require the formation of metal joints, it can also be low load, short time, and low temperature compared to the above-mentioned formal compression bonding, resulting in advantages such as improved productivity and prevention of degradation of the connection part. After the semiconductor chip is connected to the substrate, it can also be heated in an oven or the like to cure the semiconductor adhesive. The heating temperature can be a temperature at which the semiconductor sealing adhesive is cured and completely cured. The heating temperature and heating time can be set appropriately.

[0145] Example

[0146] Hereinafter, the present invention will be described using examples, but the present invention is not limited to these examples.

[0147] <Production of Semiconductor Adhesives>

[0148] The compounds used for preparing the adhesive for semiconductors are shown below.

[0149] (Curing resin component)

[0150] (a) Epoxy resin

[0151] A polyfunctional solid epoxy resin containing a trisphenol methane skeleton (manufactured by Japan Epoxy Resins Co. Ltd., product name "EP1032H60")

[0152] Bisphenol F liquid epoxy resin (manufactured by Japan Epoxy Resins Co. Ltd., product name "YL983U")

[0153] Flexible epoxy resin (manufactured by Japan Epoxy Resins Co. Ltd., product name "YL7175")

[0154] (b) Curing agent

[0155] 2,4-Diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct (manufactured by Shikoku Chemicals Corporation, product name "2MAOK-PW")

[0156] ((c) Thermoplastic resin)

[0157] Phenoxy resin (manufactured by NIPPON STEEL Chemical & Material Co., Ltd., product name "ZX1356-2", Tg: approximately 71° C., Mw: approximately 63,000)

[0158] (Inorganic filler)

[0159] Polyhedral alumina 1 (Sumitomo Chemical Co., Ltd., AA-04, average particle size: 0.41 μm)

[0160] Polyhedral alumina 2 (Sumitomo Chemical Co., Ltd., AA-07, average particle size: 0.83 μm)

[0161] Polyhedral alumina 3 (Sumitomo Chemical Co., Ltd., AA-1.5, average particle size: 1.6 μm)

[0162] Polyhedral alumina 4 (Sumitomo Chemical Co., Ltd., AA-3, average particle size: 3.7 μm)

[0163] Polyhedral alumina 5 (Sumitomo Chemical Co., Ltd., AA-5, average particle size: 6.6 μm)

[0164] Polyhedral alumina 6 (Sumitomo Chemical Co., Ltd., AA-10, average particle size: 14.5 μm)

[0165] Silicon carbide 1 (TOMOE Engineering Co., Ltd., αSiC2500N, average particle size: 0.87 μm)

[0166] Silicon carbide 2 (TOMOE Engineering Co., Ltd., βSiC2500N, average particle size: 0.82 μm)

[0167] Boron nitride 1 (Momentive, PT132, average particle size: 5.1 μm)

[0168] Boron nitride 2 (Momentive, AC6041, average particle size: 5.4 μm)

[0169] Boron nitride 3 (Momentive, TECO20191251, average particle size: 4.5 μm)

[0170] Diamond (Tomei Diamond, CMM2-4, average particle size: 2.4 μm)

[0171] (filler)

[0172] Inorganic silica filler (Admatechs Co., Ltd., SE2050, average particle size: 500 nm)

[0173] (Flux)

[0174] Glutaric acid (manufactured by Wako Pure Chemical Corporation, Wako special grade, melting point: approximately 95°C)

[0175] (Example 1)

[0176] A thermosetting resin (45 parts by mass of "EP1032H60", 15 parts by mass of "YL983U", and 5 parts by mass of "YL7175"), 2 parts by mass of a curing agent, an inorganic filler (amounts listed in Table 1, unit: mass % (based on the total amount of the semiconductor adhesive)), 10 parts by mass of an organic filler, and 4 parts by mass of a flux were added to an organic solvent (cyclohexanone) to achieve an NV (non-volatile content) concentration of 55% by mass. Subsequently, 1.0 mm and 2.0 mm diameter beads were added in an amount equal to the solid content, and the mixture was stirred for 30 minutes using a bead mill (Planetary Micro-Pulverizer P-7 manufactured by Fritsch Japan Co., Ltd.). Subsequently, 30 parts by mass of a phenoxy resin was added as a thermoplastic resin, and the mixture was stirred again using the bead mill for 30 minutes. The beads used in the stirring were removed by filtration. The prepared varnish was applied using a small precision coating device (manufactured by Yasui Seiki Inc.) and dried in a clean oven (manufactured by ESPEC CORP.) (100° C. / 10 minutes) to obtain a film-like adhesive (adhesive for semiconductors) having a thickness of 400 μm.

[0177] (Examples 2 to 21, Comparative Example 1)

[0178] Film-shaped adhesives (semiconductor adhesives) were obtained in the same manner as in Example 1, except that the types and contents of the inorganic fillers were changed as shown in Tables 1 to 4. The difference in average particle diameters in Tables 3 and 4 was calculated from the absolute value of the difference in average particle diameters of the inorganic fillers used simultaneously.

[0179] <Evaluation>

[0180] (1) Thermal conductivity measurement

[0181] The prepared film-like adhesive was cut into 1 cm × 1 cm pieces and cured at 240°C for 1 hour in a clean oven (manufactured by ESPEC CORP.) to obtain a cured product. Both sides of the obtained cured product were blackened with graphite spray, and the thermal diffusivity in the thickness direction was measured. The thermal diffusivity was measured using a laser flash method (Xe-flash method) (manufactured by NETZSCH, LFA447nanoflash). Pulse light irradiation was performed under the conditions of a pulse width of 0.1 (ms) and an applied voltage of 236 V. The measurement was performed at an ambient temperature of 25°C ± 1°C. Then, the specific heat and density were multiplied by the thermal diffusivity using the following formula (I), thereby obtaining the value of thermal conductivity. The results are shown in Tables 1 to 4.

[0182] λ=α×Cp×p...Formula (I)

[0183] [In formula (I), λ represents thermal conductivity (W / mK), α represents thermal diffusivity (m2 / s), Cp represents specific heat (J / kg·K), and ρ represents density (g / cm 3 ). ]

[0184] The specific heat (J / kg·K) was measured using differential scanning calorimetry (DSC) in the following procedure. The semiconductor adhesive was weighed into an aluminum pan and measured using a differential scanning calorimeter (Pyris1, manufactured by PerkinElmer Japan Co., Ltd.) at a rate of 10°C / min from room temperature (25°C) to 60°C. Sapphire was used as a reference. The known specific heat of sapphire was used to calculate the specific heat of the sample at 25°C.

[0185] The density (g / cm2) was measured using an electronic hydrometer (manufactured by Alfa Mirage Co., Ltd., SD-200L) at a water temperature of 25°C. 3 ).

[0186]

[0187]

[0188]

[0189] [Table 4]

[0190]

[0191] In Examples, it was confirmed that excellent heat dissipation was obtained. In Comparative Example 1, it was confirmed that sufficient heat dissipation was not obtained.

[0192] Explanation of symbols

[0193] 10-Semiconductor chip, 15-Wiring, 20, 60-Substrate, 30-Connection bump, 32-Bump, 34-Through electrode, 40-Sealing material, 42-Semiconductor adhesive, 50-Interposer, 70-Solder resist, 90-Crimp tool, 100, 200, 300, 400, 500, 600-Semiconductor device, 700-Stacked chip.

Claims

1. A semiconductor adhesive, which is used for sealing the connection parts in a semiconductor device having a connection structure in which the connection parts of a semiconductor chip and a wiring circuit board are electrically connected to each other and / or a connection structure in which the connection parts of a plurality of semiconductor chips are electrically connected to each other, The semiconductor adhesive contains a curable resin component, a flux and an inorganic filler. The content of the inorganic filler is 80 to 95% by mass based on the total amount of the semiconductor adhesive. The thermal conductivity of the semiconductor adhesive after curing is 1.5W / mK or more. As the inorganic filler, polyhedral alumina having a volume-based average particle size r1 of 5 to 20 μm and polyhedral alumina having a volume-based average particle size r2 of 0.1 to 4.5 μm are prepared. The difference between the average particle diameter r1 and the average particle diameter r2, namely r1-r2, is 4 to 10 μm.

2. The semiconductor adhesive according to claim 1, wherein The inorganic filler contains polyhedral alumina.

3. The adhesive for semiconductor according to claim 1 or 2, wherein: The inorganic filler includes at least one selected from the group consisting of silicon carbide, boron nitride, diamond, and aluminum nitride.

4. The adhesive for semiconductor according to claim 1 or 2, wherein: The inorganic filler has peaks in each of the ranges of 0.1 to 4.5 μm and 5 to 20 μm in a volume-based particle size distribution. 5 . The adhesive for semiconductor according to claim 1 , wherein the thermal conductivity after curing is 3.0 W / mK or more.

6. The adhesive for semiconductor according to claim 1 or 2, wherein: The flux is carboxylic acid.

7. The adhesive for semiconductor according to claim 1 or 2, wherein: The curable resin component contains a thermosetting resin, a curing agent and a thermoplastic resin.

8. A method for manufacturing a semiconductor device, the semiconductor device comprising a connection structure in which respective connection portions of a semiconductor chip and a wiring circuit board are electrically connected to each other and / or a connection structure in which respective connection portions of a plurality of semiconductor chips are electrically connected to each other, the method comprising: A step of sealing at least a portion of the connection portion using the semiconductor adhesive according to any one of claims 1 to 7.

9. A semiconductor device comprising: A connection structure in which respective connection portions of a semiconductor chip and a printed circuit board are electrically connected to each other and / or a connection structure in which respective connection portions of a plurality of semiconductor chips are electrically connected to each other; and a sealing material that seals at least a portion of the connection portion, The sealing material contains a cured product of the adhesive for a semiconductor according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for bonding semiconductor wafer and method for manufacturing semiconductor device

    JP2008294382A

  • Composition for interlayer filler of layered semiconductor device, layered semiconductor device, and method for manufacturing layered semiconductor device

    CN105073883A

  • Resin composition, b stage sheet, metal foil with applied resin, metal substrate and LED substrate

    JP2013071991A